2021
DOI: 10.3390/ijms22126614
|View full text |Cite
|
Sign up to set email alerts
|

The Main Cytotoxic Effects of Methylseleninic Acid on Various Cancer Cells

Abstract: Studies of recent decades have repeatedly demonstrated the cytotoxic effect of selenium-containing compounds on cancer cells of various origins. Particular attention in these studies is paid to methylseleninic acid, a widespread selenium-containing compound of organic nature, for several reasons: it has a selective cytotoxic effect on cancer cells, it is cytotoxic in small doses, it is able to generate methylselenol, excluding the action of the enzyme β-lyase. All these qualities make methylseleninic acid an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 112 publications
(161 reference statements)
0
35
0
Order By: Relevance
“…Selenite-induced cell death is independent of these death proteases [17,[29][30][31]. On the other hand, the anti-carcinogenic effects of Se mediated byCH 3 SeH or its derivatives have been shown in the papers by References [32][33][34][35][36][37][38]. They have shown that the CH 3 SeH-precusor MSeCN and MSeC can inhibit mammary cell growth, arresting cells in G1 phase and inducing apoptosis [21,22,30,[39][40][41][42].…”
Section: Metabolism Of Selenium Compoundsmentioning
confidence: 99%
“…Selenite-induced cell death is independent of these death proteases [17,[29][30][31]. On the other hand, the anti-carcinogenic effects of Se mediated byCH 3 SeH or its derivatives have been shown in the papers by References [32][33][34][35][36][37][38]. They have shown that the CH 3 SeH-precusor MSeCN and MSeC can inhibit mammary cell growth, arresting cells in G1 phase and inducing apoptosis [21,22,30,[39][40][41][42].…”
Section: Metabolism Of Selenium Compoundsmentioning
confidence: 99%
“…It has been shown that Se dioxide can prevent the oxidative damage of DNA caused by the interaction of Fe (II), Cr (III) and Cu (II) with hydrogen peroxide by forming a coordination complex with metals [ 4 , 5 ]. Among all known organic Se-containing compounds, a special place is occupied by methylseleninic acid (MSA), which is formed as a result of the oxidative decomposition of methyl selenocysteine and has a number of important advantages over other selenium agents [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more and more works have appeared on the study of the anticancer effect of selenium, selenoproteins, and SeNP [ 32 , 33 , 34 ]. The anticancerous property of SeNP is due to the induction of glutathione S-transferase (GST) by selenium [ 35 ].…”
Section: Discussionmentioning
confidence: 99%